Real-world management of patients with complete response under immune-checkpoint inhibition for advanced melanoma - Reitmajer, Markus; Livingstone, Elisabeth; Thoms, Kai Martin; Heppt, Markus; Meiss, Frank; Gesierich, Anja; Drexler, Konstantin; Heinzerling, Lucie; Meier, Friedegund; Menzer, Christian; Schlaak, Max; Zimmer, Lisa; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2025)
Background: Up to now, the optimal duration of immune checkpoint inhibitors (ICI) has not been evaluated in prospective studies. However, current clinical practice requires decisions to be made regarding the duration of ICI in complete responders. Material and Methods: A survey was sent to 80 DeCOG skin cancer centers to assess how decisions are made on treatment duration of ICI in melanoma after having reached complete response, and staging intervals after ICI discontinuation. All responses received by March 10, 2024 (51 centers) were included. Results: The duration of ICI after having achieved complete remission varies between centers from three to 36 months. In total, 66% of the DeCOG centers continue treatment for up to 6 months, after having achieved complete remission (CR) with ICI. In the first year after discontinuation of ICI, most centers perform staging intervals (CT/MRI) every 3 months. More than 60% of centers continue staging at least once per year even in the 4th and 5th year after discontinuation. Conclusions: There are significant differences between the centers regarding staging intervals and duration of ICI upon CR. Prospective studies are necessary to determine the optimal time point of ICI discontinuation and follow-up.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Advanced Melanoma; follow-up; immune checkpoint inhibitor (ICI); pause; PET/CT; surveillance; treatment discontinuation